PENGARUH TRANSFER PRICING, THIN CAPITALIZATION DAN KARAKTER EKSEKUTIF TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR PERTAMBANGAN - Fatihah Al Husna; Ilham H Napitupulu; Rahmadani Rahmadani; Heddy Lumbantoruan (Jurnal Akuntansi dan Bisnis, 2026)
This study aims to examine the effect of transfer pricing, thin capitalization, and executive character on tax avoidance. This research employs a quantitative approach using secondary data in the form of annual financial statements of mining sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The sample was selected using a purposive sampling method, resulting in 24 companies as the research sample from the total population. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS) 25. The results show that the thin capitalization variable has a significant effect on tax avoidance, while transfer pricing and executive character have no significant effect on tax avoidance..